Cote d’Ivoire Urbanization Review : Diversified Urbanization - World Bank (Washington, DC, 2015)
Well-managed urbanization can accelerate Cote d’Ivoire’s ascendance to middle incomes. Such a large gap in gross national income (GNI) per capita means that the underlining economic drivers of urbanization are not being fully harnessed in Cote d’Ivoire. Small cities at low urbanization level facilitate internal scale economies, such as hosting a large firm transforming local agricultural products. Secondary cities at intermediate urbanization level facilitate localization economies by enabling linkages between firms operating in the same sector. Large cities at advanced urbanization level facilitate urbanization economies through a diverse economic base nurturing innovation. Drawing on the findings of the World Development Report 2009 applied to the Ivorian context, the authors identify three types of cities in the country: global connector cities generating urbanization economies needed for innovation, increasing return to scale activities, and global competitiveness; regional connector cities generating localization economies needed for efficient regional trade and transport; and domestic connector cities generating internal scale economies needed to unleash the agricultural potential of regions. Cote d’Ivoire’s small cities and market towns can be anchors generating scale economies for agribusiness. While southwest regions strongly contribute to the production and export of cash crops, savanna areas can help scale up food and cereal production to supply urban centers domestically and regionally.